A Search into a Suitable Channel Access Control Protocol for LoRa-Based Networks - Farooq, Muhammad Omer; Pesch, Dirk (2018 IEEE 43rd Conference on Local Computer Networks (LCN), 2018)
Low-power wide-area networking (LPWAN) has gained much attention recently and offers significant potential to support a large number of Internet of Things (IoT) applications. For device simplicity, LPWANs tend to use a simple channel access control protocol such as Aloha, which impacts performance. While several LPWAN technologies are available, we specifically focus on the Long Range (LoRa) in this paper. Our goal in this study is to search for a channel access control protocol in conjunction with the LoRa physical layer that can improve network performance in terms of reliability, throughput, energy consumption, and yet retain simplicity. We analyze a range of channel access control protocols, such as pure Aloha, delay before transmit, random frequency hopping, and carrier sense multiple access (CSMA). Our experiments use available periodic and event-based data traffic generation models for Internet of Things applications. Our results show that, CSMA and random frequency hopping demonstrate significantly better performance for both periodic and event-based data traffic models. Moreover, CSMA also exhibits scalability features in terms of the number of nodes in a network and data traffic generation models.